Validity of wind power for heavy winter demand in eastern Japan power systems - Kondoh, Junji (Frontiers in Energy Research, 2023)
On a day with unusually low temperatures in March 2022, there was a risk of a shortage in the power supplied by the eastern Japan (Tohoku and Tokyo) power systems owing to the spiked demand. Mass-installed photovoltaic power systems cannot be considered as winter supply capacity because they generate almost no electricity during such heavy demand in winter. Conversely, wind power, which is currently installed in much less capacity, is promising in these areas owing to the high output due to the East Asian winter monsoon. This study clarifies that, in the Tohoku power system, the winter capacity values of wind power are sufficiently high and higher than the annual capacity factors. The study concluded that increasing offshore wind farms along the Tohoku area can effectively supply part of the tight winter electricity demand that needs to be fulfilled by power systems in eastern Japan. Moreover, it increases the share of renewable energy sources.